Correcting anemia and native vitamin D supplementation in kidney transplant recipients: a multicenter, 2 × 2 factorial, open‐label, randomized clinical trial. (15th June 2021) - Obi, Yoshitsugu; Ichimaru, Naotsugu; Sakaguchi, Yusuke; Iwadoh, Kazuhiro; Ishii, Daisuke; Sakai, Ken; Iwami, Daiki; Harada, Hiroshi; Sumida, Keiichi; Sekine, Akinari; Masutani, Kosuke; Akutsu, Naotake; et al.
Summary: Anemia and vitamin D deficiency are associated with allograft failure, and hence, are potential therapeutic targets among kidney transplant recipients (KTRs). We conducted a multicenter, two‐by‐two factorial, open‐label, randomized clinical trial to examine the effects of anemia correction and vitamin D supplementation on 2‐year change in eGFR among KTRs (CANDLE‐KIT). We enrolled 153 patients with anemia and >1‐year history of transplantation across 23 facilities in Japan, and randomly assigned them to either a high or low hemoglobin target (>12.5 vs. <10.5 g/dl) and to either cholecalciferol 1000 IU/day or control. This trial was terminated early based on the planned interim intention‐to‐treat analyses (α = 0.034). Among 125 patients who completed the study, 2‐year decline in eGFR was smaller in the high vs. low hemoglobin group (i.e., −1.6 ± 4.5 vs. −4.0 ± 6.9 ml/min/1.73 m 2 ; P  = 0.021), but did not differ between the cholecalciferol and control groups. These findings were supported by the fully adjusted mixed effects model evaluating the rate of eGFR decline among all 153 participants. There were no significant between‐group differences in all‐cause death or the renal composite outcome in either arm. In conclusion, aggressive anemia correction showed a potential to preserve allograft kidney function.